“Las competencias de los jueces penales y la vulneración al principio de especialidad en el desarrollo jurisdiccional de garantías penitenciarias” PORTADA - Silvia Janeth, Villacis Raza (2020)
Based on what is established by the Ecuadorian Constitution regarding prison guarantees contemplate by Art. 186 last paragraph. The Organic Code of the Judicial Function, it develops the competency of judges of prison guarantees by Art.230, and the Organic Penal Code, by Art. 666, does not exist Constitutional competency due to the Constitution talks about of the same competency so that a legal apparatus has been established for compliance with the Constitution of the Republic of Ecuador, in accordance with Articles 82, 424, 425. The normative hierarchy considers that corresponds to the competition principle in special, to the ownership of the exclusive competency of the Decentralized Autonomous Governments, of the superior norm, lacking legal efficacy. The problem is exposed specifically for the resolution 018-2014 of Judicial Council, it establishes a double competency in the judges of criminal guarantees, to serve also as a judges of prison guarantees, violating the specialty principle that is in the Art 11 of Organic Code of Judicial Function contravening the hierarchy of the norm, the security, and the legal efficacy. The present research is justified how much is relevant describe, through of the application of research instruments, because the resolution 018-2014 of Judicial Council breaches with the specialty principle and competency perfectly defined in the legal apparatus and constitutional, contravening to the point that it lacks legal efficacy to breach with these fundaments, to achieve this objective, it has been planned to perform a documentary bibliographic review of similar works which is intended to perform, to check the current normative and apply research instruments to people that know and they have specialized in the topic, with the results it is aspired to check empirically.